IMPLEMENTASI ASESMEN AUTENTIK RANAH SIKAP PADA KURIKULUM ISMUBA DI SD MUHAMMADIYAH KADISOKA - Edo Alvizar Dayusman; Maemonah Maemonah (Institut Madani Nusantara, 2023)
This study describes the implementation of an authentic assessment of the attitude domain in the ismuba curriculum at SD Muhammadiyah Kadisoka. This study aims to analyze the implementation of an authentic assessment of the attitude domain in the ismuba curriculum so that it is able to form a positive character in every student at SD Muhammadiyah Kadisoka. The research method that the researcher uses in this study is a descriptive qualitative method, namely by conducting various analyzes found in the field relating to the implementation of authentic assessments in the realm of attitudes in the school. The data sources consist of primary data and secondary data, namely the ismuba coordinator, ismuba curriculum documents at SD Muhammadiyah Kadisoka and documents related to the school curriculum. Based on the results of the study, it can be concluded that the implementation of an authentic assessment in the domain of attitudes in the ismuba curriculum is carried out in a structured and good manner, even the school provides an activity book that must be filled out by parents/guardians to assess student attitudes when outside the school environment.